Postoperative Hypothermia in Surgical Patients at Azadi Teaching Hospital (Medico Legal Update, 2020)
Introduction: The sensation to cold, shake occurrence and shivering are events that are commonlydeveloped following general anesthesia administration postoperatively. Hypothermia has been considered asthe most frequent outcome of surgery underwent by anesthesia. Inadvertent hypothermia has been taken intoaccount as common side effect in the postoperative period immediately and it is related to wide impairmentsand anomalies of different body organs. Concentration on predictive factors of hypothermia would beimportant to reduce the incidence rate and correct preventable unnecessary risks for patients in the healthsettings following surgical operations. The aim of study is to assess the magnitude and associated factors ofpostoperative hypothermia recovery room in patients underwent general anesthesia. Methods: A hospitalbased prospective cross-sectional study was conducted on200patients with different age groups of bothgenders who underwent a scheduled non-cardiac surgery and general anesthesia consecutively during theperiod between the October 1stand the November1st2016. Results: The study revealed that the overall corehypothermia in the study sample was31%. The study showed that the post-operative temperatures decreasedstatistically significantly in all study patients and separately in adults, children, males, or females P